2020
DOI: 10.1111/wrr.12807
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast‐specific Stat1 deletion enhances the myofibroblast phenotype during tissue repair

Abstract: Signal transducer and activator of transcription 1 (Stat1) is a ubiquitously expressed latent transcription factor that is activated by many cytokines and growth factors. Global Stat1 knockout mice are prone to chemical‐induced lung and liver fibrosis, suggesting roles for Stat1 in tissue repair. However, the importance of Stat1 in fibroblast‐mediated and vascular smooth muscle cell (VSMC)‐mediated injury response has not been directly evaluated in vivo. Here, we focused on two models of tissue repair in condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…STAT1 can promote apoptosis and inflammation (40). Moreover, Medley et al found that STAT1 plays a role in wound repair as a fibroblastmediated inhibitor (41). Along with previous studies, our findings indicate that STAT1 may participate in wound repair through the inflammatory process and the regulation of fibroblasts.…”
Section: Discussionsupporting
confidence: 85%
“…STAT1 can promote apoptosis and inflammation (40). Moreover, Medley et al found that STAT1 plays a role in wound repair as a fibroblastmediated inhibitor (41). Along with previous studies, our findings indicate that STAT1 may participate in wound repair through the inflammatory process and the regulation of fibroblasts.…”
Section: Discussionsupporting
confidence: 85%
“…4 Actually, the fibroblast-myofibroblast-fibrocyte complex is only one element in a much larger chessboard, which includes other components, both cellular (endothelium of blood and lymphatic vessels, monocyte-macrophages, lymphocytes, nerve ganglia, etc) and noncellular (extracellular matrix and others) and their anabolic processes must be continually balanced by catabolic processes and by cellular reprocessing, under the control of signal molecules (from free radicals to cytokines and up to growth factors). 5,6 In other words, given the structural and functional complexity of the skin at molecular level, it is clear that fibroblast stimulation alone may be inadequate to prevent or treat the imperfections without an "integrated" approach. In the field of esthetic medicine, an important fact is that fragments of hyaluronic acid between 20 and 30 monomers activate the fibroblasts by binding to CD44 receptors and thus the production of reticular collagen type III.…”
mentioning
confidence: 99%
“…In the skin model, the expression of collagen and α-SMA in the granulation tissue around the wound of mice with fibroblast STAT1 gene defects increased, and the perivascular fibrosis increased significantly. These results indicated that STAT1 plays a role in tissue repair [33]. As a key element of IFN-α-2b signal transduction, the function of STAT1 is mainly determined by its phosphorylation state.…”
Section: Discussionmentioning
confidence: 77%